CEP55-associated lethal fetal syndrome: a case report of a Chinese family - Wang, Yeping; Sheng, Fang; Ying, Lingjing; Lou, Qiaoli; Yu, Zhaonan; Wang, Kaixuan; Wang, Haoyi (Frontiers in Genetics, 2023)
Background: Research on fetal loss related to germline mutations in single genes remains limited. Disruption of CEP55 has recently been established in association with perinatal deaths characterized by hydranencephaly, renal dysplasia, oligohydramnios, and characteristic dysmorphisms. We herein present a Chinese family with recurrent fetal losses due to compound heterozygous nonsense CEP55 variants. Case presentations: The Chinese couple had a history of five pregnancies, with four of them proceeding abnormally. Two stillbirths (II:3 and II:4) sequentially occurred in the third and fourth pregnancy. Prenatal ultrasound scans revealed phenotypic similarities between fetuses II:3 and II:4, including oligohydramnios, bilateral renal dysplasia and hydrocephalus/hydranencephaly. Clubfoot and syndactyly were also present in both stillborn babies. Fetus II:3 presented with endocardial cushion defects while fetus II:4 did not. With the product of conception in the fourth pregnancy, whole exome sequencing (WES) on fetus II:4 identified compound heterozygous nonsense CEP55 variants comprised of c.190C>T(p.Arg64*) and c.208A>T(p.Lys70*). Both variants were expected to result in lack of the TSG101 and ALIX binding domain. Sanger sequencing confirmed the presence and cosegregation of both variants.Conclusion: This is the fifth reported family wherein biallelic CEP55 variants lead to multiple perinatal deaths. Our findings, taken together with previously described phenotypically similar cases and even those with a milder and viable phenotype, broaden the genotypic and phenotypic spectrum of CEP55-associated lethal fetal syndrome, highlighting the vital biomolecular function of CEP55.